Zack's story - Dokey, Cameron (Boys camp, 2013)
"Zack is finally attending summer camp, a dream he's always had. But he quickly realizes that the wilderness has unexpected twists and turns and he must band together with his friends to stay safe and have fun"--Provided by publisher.